(untitled) (Książnica Śląska, 2025)
The text briefly presents the history of libraries and reading in Bielsko- -Biała and the activities of the Beskid Library in disseminating knowledge about the region. The article shows some databases created by the library, such as: Beskidzkie ABC, Datownik Regionalny and Regio-sources. It also describes the history of regional bibliography and the current state of work on this publication initiated in the 1960s.